An assessment of the effectiveness of revenue collection strategies employed by local authorities: a case of Beitbridge Town Council from the period 2010-2017 - Wozhele, Venencia (Midlands State University, 2018)
The study was conducted in order to assess the effectiveness of revenue collection strategies employed by local authority using Beitbridge Town Council (B.T.C) as a case study. The main objective of the research was to analyze the revenue collection strategies employed by council and evaluate or to judge to what extent did those strategies managed to improve revenue collection at B.T.C. the research revealed that B.T.C used debt collection method, the use of Information Communication Technology (I.C.T) and collection of debt by installments. The researcher used qualitative approach which involves both primary and secondary sources of data such as the documentary reviews, interviews, and questionnaire as well as telephone conversation so as to gather data. In addition to that the researcher also used non-probability sampling technique which includes purposive and convenience sampling technique. Data was presented in tables and pie charts and also it was analyzed by using context analysis. The study concluded that the strategies used by council did not succeed to the greater extent since it manages to boast and improve their revenue base. The research also found out that there are some challenges that hindered the revenue collection techniques such as lack of transport, political interference, poor service delivery, the statutory instruments 64 of 2016, the residents are not willing to pay rents and also incorrect billing and corruption. In summing up of the research findings recommendations were made by residents that the council should improve its service delivery, reduce the charges, sue defaulters, have effective communication, improve billing, and the central government should empower local authorities.